The lean entrepreneur : how visionaries create products, innovate with new ventures, and disrupt markets - Cooper, Brant. (Wiley, 2013)
"Advice for entrepreneurs looking to build a business people actually want to invest inDesigned to reduce waste by testing the market for a product early and often, the concept of the lean startup has been embraced around the world, and successful entrepreneurs and authors Brant Cooper and Patrick Vlaskovits join the conversation with their own personal experiences. The Lean Entrepreneur is designed to make lean startup and customer development principles immediately actionable no matter what the industry, size, or stage.This must-read book presents a lexicon of concepts and a universally applicable road map to success, as well as illustrative examples of innovative approaches to industry-specific disruption ranging from technology startups to consumer packaged goods to music to investment and finance. Providing a step-by-step approach to best practices, and giving readers a business model analysis guide, the book is rich in cases studies, illustrative graphics, worksheets, and exercises for a truly immersive guide to starting or improving a company. Invaluable reading for all readers in all businesses, the book teaches entrepreneurs how to approach risk head-on and test market ideas immediately, foster stronger customer relations, test different business model risks, and create a customer funnel based on buyers' process in order to eliminate unnecessary time and effort.A lean entrepreneur has already bought into lean startup, customer development, design thinking, and other iterative, customer-centric methods of product development. The lean entrepreneur wants to know how to apply these to their business. In other words: how to get started tomorrow. This book shows the way. Expands on the core ideas of the "Lean Startup" concept, adding the use of powerful, low-cost analytics to the mix Explains how earlier, more frequent market research can save a business time and money Incorporates cases studies, graphics, worksheets, and exercises to help readers better understand the key concepts expounded in the text Packed with information that can help business at all levels of development--from initial ideas to established companies looking to innovate--The Lean Entrepreneur is the field guide for creating innovative businesses"--